Effects of Packaging Types on Moisture Content, Microbe Total and Peroxide Value of Instant Ganyong (Canna edulis Kerr) Yellow Rice - Lilis Sulandari (UPT Penerbitan Universitas Jember, 2016)
The effects of packaging types on moisture content, microbe total and peroxide value of instant ganyong yellow rice during storage were investigated. Instant ganyong yellow rice was packed in three different packaging types; aluminium foil (Al foil ), nylon and the combination of oriented polypropylene (OPP) & vacuum metalize OPP (OPP-VMOPP) and stored at room temperature for 8 weeks. The results showed that samples in the Al foil had lower moisture content than other packaging materials, but until storage 8 weeks moisture content of three packaging types was not different. Microbe total on samples showed significance. Samples in the packaging of nylon material had highest microbe total compared to other packaging materials, but all of the packaging types had microbe total below the acceptable level of the microorganism (6 log CFU/g) during storage 8 weeks. Peroxide value of three packaging types increased during storage, but they were not different until 8 weeks storage. They were below peroxide value for oil 1 mg oxigen/100g oil or fat. Based on the microbe total and peroxide value, instant ganyong yellow rice were packed with all three types of packaging showed safe to eat up to 8 weeks of storage at room temperature.